Historical consciousness and textbooks. An analysis from the conceptions about the period of “La Violencia” in Colombia (Encuentros, 2019)
The final results of a research that aimed at analyzing the conceptions and ideas on the historical period of “La Violencia” portrayed in ninth grade social studies textbooks published in Colombia since 1989 to 2016 are socialized. The research was methodologically grounded on the analysis of qualitative content and, theoretically, on the general principles of the historical consciousness development. From these referents, it is established that the studied textbooks have not been able to consolidate critical explanatory principles of analysis around this historical phenomenon. The aforementioned problem generates, in these pedagogical devices, a series of argumentative absences around the historical processes and agencies, which are key to understand the connections of that past with a present time marked by violent internal struggles associated with a social, political and economic conflict that has not been completely overcome in ColombiaKeywords: Textbooks; History teaching; Historical consciousness; Violence, Colombia.